ANALYSIS OF OPTIMAL STOCK PORTFOLIO INVESTMENT IN LQ45 INDEX USES THE MARKOWITZ MODEL AND SINGLE INDEX MODEL - Fadlan Alkindi; Isfenti Sadalia; Iskandar Muda (PT. Radja Intercontinental Publishing, 2023)
Based on the results of the optimal portfolio analysis of the Markowitz model and Single Index Model, it can be concluded as follows: Based on the optimal portfolio formation of the Markowitz Model, 4 shares form a portfolio return expectation of 0.0074, while the portfolio risk is 0.0428 and the proportion of funds formed is BBCA 50.81%, EXCL 9.83%, ICBP 30.59%, and KLBF 8.77%. Based on the formation of a single index model portfolio, 2 optimal portfolio formations were obtained with a portfolio return of 0.1486 and a risk of 0.0873, while the proportion of funds formed by ANTM was 10.5%, and BBCA was 89.5%.. Based on research results, it proves that the single index model can produce a profit of 14.86% with a risk level of 8.73% compared to the Risk-Free Asset Return Rate of 5.17%. Meanwhile, the Markowitz model can produce a portfolio return of 0.74% with a portfolio risk of 4.28%, which does not provide optimal profits because the expected return from the Markowitz model portfolio is lower than the Risk-Free Asset Return Rate.Lack of significant planning in investing by a company. This because in planning an investment project of course requires substantial funds, so if not budgeted and calculated properly, it can result in investment failure projects that can cause a company to experience large losses. This study discusses capital budgeting of a project in CV. ABC will buy a new machine. In the This study discussed how to calculate the initial investment, estimate the income that the company will get during the project, how long is the capital issued by the company for investment projects will be returned, and at most what is important is whether it is feasible or not is the investment project planning. Method used in capital budgeting calculations is the payback period, discounted payback period, Net Present Value (NPV), and Internal rate of Return (IRR). In the The results showed that CV ABC accepted the plan to purchase a corn drying machine by calculating the payback period for 5 years, the NPV and IRR are considered feasible.